Social interaction and conditional self-discrimination under effects of methylphenidate in norvegicus rats (2011)
Conditional self-discrimination capability was studied in 24 four weeks old subjects Rattus norvegicus. They were assigned to three different conditions of social interaction (isolation, living in pairs, and groups of four subjects). Subjects were trained under two programs of operant conditioning, each one associated with presence or absence of methylphenidate. The dependent variable was measured during the phase of extinction. Significant differences were found for self-discrimination capacity, but not in relation to social interaction. It is possible to conclude that Rattus norvegicus are able to discriminate their internal state, and learn to use this state as a discriminative stimulus. Despite the lack of significant differences in social interaction, the trends of the observed data from a qualitative point of view, suggest the possibility of interaction between the variables studied. © International Journal of Psychology and Psychological Therapy.